3D interlock design 100% PVDF piezoelectric to improve energy harvesting. (29th May 2018) - Talbourdet, Anaëlle; Rault, François; Lemort, Guillaume; Cochrane, Cédric; Devaux, Eric; Campagne, Christine
Abstract: Piezoelectric textile structures based on 100% poly(vinylidene fluoride) (PVDF) were developed and characterised. Multifilaments of 246 tex were produced by melt spinning. The mechanical stretching during the process provides PVDF fibres with a piezoelectric β -phase of up to 97% has been measured by FTIR experiments. Several studies have been carried out on piezoelectric PVDF-based flexible structures (films or textiles), the aim of the study being the investigation of the differences between 2D and 3D woven fabrics from 100% optimised (by optimising piezoelectric crystalline phase) piezoelectric PVDF multifilament yarns. The textile structures were poled after the weaving process, and a maximum output voltage of 2.3 V was observed on 3D woven under compression by DMA tests. Energy harvesting is optimised in a 3D interlock thanks to the stresses of the multifilaments in the thickness. The addition of a resistor makes it possible to measure energy of 10.5 μ J.m −2 during 10 cycles of stress in compression of 5 s each.